Digital Activism in the Brave Pink Hero Green Movement: Forms of Political Participation by Influencers and the Public on Social Media - Gandhi Rahmat Romadhoni; Rona Rizkhy Bunga Chasana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the forms of digital political participation emerging from the involvement of influencers and the public in disseminating the Brave Pink-Hero Green visual campaign within the #ResetIndonesia movement on social media. Employing a descriptive qualitative approach, the study collected data through in-depth interviews with six purposively selected informants, consisting of three influencers and three members of the public actively engaged in the campaign. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while source triangulation was used to ensure validity. The findings indicate that the Brave Pink-Hero Green campaign spread organically across social media platforms without formal organizational structures, driven by shared socio-political concerns and facilitated through visual symbols representing courage, solidarity, and criticism of government policies. Digital political participation is manifested through activities such as reposting content, changing profile pictures, sharing information, commenting, and engaging in online discussions. Influencers played a strategic role in amplifying messages, simplifying issues, and increasing public awareness, whereas the public contributed by extending message dissemination and fostering collective engagement. The interaction between influencers and the public reflects the characteristics of connective action and participatory culture, highlighting how digital media enables collaborative and decentralized political participation. This study contributes to the digital activism literature by examining visual symbol-based activism through the Brave Pink-Hero Green campaign, extending current understandings of digital political participation beyond hashtag-centered activism.